Shoulder Tendinopathies and Occupational Biomechanical Overload: A Critical Appraisal of Available Evidence - Curti, Stefania; Mattioli, Stefano; Violante, Francesco Saverio (La Medicina del Lavoro, 2023)
Background: The aim of this study is to evaluate the association between occupational exposure to biomechanical risk factors and shoulder tendinopathies. Methods: We updated recent systematic reviews about specific shoulder disorders and work-related risk factors. MEDLINE was searched up to September 2022. Studies satisfying the following criteria were included: i) the diagnosis was based on physical examination plus imaging data (when available), and ii) the exposure assessment was based on video analysis and/or directly measured. Results: Five studies met the inclusion criteria: three cross-sectional studies identified from published systematic reviews and two cohort studies retrieved from the update. Two studies investigated shoulder tendinitis, one supraspinatus tendinitis, and the other two rotator cuff syndrome. The diagnosis was based on physical examination, not supported by imaging techniques for all the included studies. In four out of five studies, the exposure was assessed by experienced ergonomists with the support of video recordings. In two studies, the exposure assessment was further supplemented by force gauge measurements or direct measurements of upper arm elevation. Only the combined exposure of working with arms above shoulder level with forceful hand exertion appears to be associated with rotator cuff syndrome: i) a cohort study reported an HR=1.11 (95%CI 1.01-1.22) for each unit increase in forceful repetition rate when the upper arm is flexed ≥45° for ≥29% of the working time; and ii) a cross-sectional study showed an OR=2.43 (95%CI 1.04-5.68) for the combination of upper arm flexion ≥45° for more than 15% of the time with a duty cycle of forceful exertions more than 9% of the time. Conclusions: There is moderate evidence of a causal association between shoulder tendinopathy and combined exposures of working above shoulder level with forceful hand exertion. The evidence is insufficient for any single biomechanical exposure on its own. High-quality cohort studies with direct exposure measures and objective diagnostic criteria are needed. The occupational origin of shoulder tendinopathies is still an open question that must be properly answered.